The Study on Corrosion Resistance of Ti-6Al-4V ELI Alloy with Varying Surface Roughness in Hydrofluoric Acid Solution - Han Wang; Quanshi Cheng; Zhuo Chang; Kedi Wang; Xuemin Gao; Xueling Fan (Metals, 2024)
The corrosion resistance of titanium alloy poses a crucial challenge, significantly affecting its prospect for service and application. The present study aimed to investigate the corrosion resistance of Ti-6Al-4V ELI alloys with varying surface roughness in hydrofluoric acid solution, in order to assess the influence of roughness on their corrosion resistance performance. The weight loss percentage, surface morphology evolution, and roughness variation of Ti-6Al-4V ELI alloys before and after exposure to hydrofluoric acid corrosion were characterized. While the weight loss and weight loss percentage of the Ti-6Al-4V ELI alloy increased with prolonged corrosion, the overall weight loss rate decreased. The accumulation of TiF3 phases and depletion of the Ti-6Al-4V ELI matrix mutually led to the alterations of the surface roughness. Due to the inability to prevent fluoride ions from contacting with the Ti-6Al-4V ELI alloy, continuous corrosion occurred in hydrofluoric acid. Based on these experimental results and analysis, the corrosion mechanism of the Ti-6Al-4V ELI alloy corroded by hydrofluoric acid solution was elucidated. Furthermore, an analysis was conducted to explore the influence of corrosion time on mechanical properties by analyzing the decay in compressive properties of the Ti-6Al-4V ELI titanium alloy after hydrofluoric acid corrosion treatment. The bearing capacity of the Ti-6Al-4V ELI alloy deteriorated over the corrosion time.